Pengaruh ROE dan EPS Terhadap Harga Saham PT Unilever Indonesia Tbk Periode 2006-2020 - Chintia Dwi Anggraeni; Ryan Elfahmi (Jurnal Ilmiah Raflesia Akuntansi, 2021)
Abstract - This study was conducted to determine the effect of Return on Equity and Earning Per Share on the stock price of PT Unilever Indonesia Tbk for the period 2006-2020. The method used in this research is quantitative method with descriptive analysis test technique, classical assumption test by performing normality test, non-multicollinearity test, non-heteroscedasticity test, non-autocorrelation test, model feasibility test by performing multiple correlation test, coefficient of determination test, and test simultaneous test (f test), and test the effect of causality by performing multiple linear regression test and partial test (t test). The results of this study indicate that the Return on Equity and Earning Per Share simultaneously has effects on the stock price of PT Unilever Indonesia Tbk, this happens because the value of F count > F table with a significance value less than 0.05. Return on Equity partially has no effect on the stock price, this happens because the value of t count < t table with a significance value less than 0.05. Earning Per Share partially has effects on the stock price of PT Unilever Indonesia Tbk, this happens because the value of t count > t table with a significance value less than 0.05.   Keywords - Return on Equity (ROE), Earning Per Share (EPS), Stock Prices